Comparative analysis of the performance of investment instruments in the fourth industrial revolution (a comparative study of risk and return between stocks, gold, and cryptocurrency) (Lighthouse Publishing, 2023)
This research is done to determine the best-performing investment instruments in the Fourth Industrial Revolution by analyzing the performance of stocks, gold, and cryptocurrencies. In this era of information, investing is a well-known strategy used to allocate wealth. However, the knowledge of investment still needs to be improved. Thus, this research is done to provide comprehensive information about investment instruments performances. The sample used in this research is the monthly closing price of IDX30 stocks, gold, and cryptocurrency from January 2018 – December 2021. The analytical method used in this research is a comparative method which is done by using secondary data. Microsoft Excel was used to calculate the formula of each variable. Afterward, the data obtained were processed using the IBM SPSS application, the Kruskall-Wallis’s test. Our research indicates no significant difference between IDX30 stocks, gold, and cryptocurrency when measured from return. However, our research finds significant differences between IDX30 stocks, gold, and cryptocurrency when measured from risk. Therefore, in conclusion, it is advised for investors to be wary of the risks presented by each investment instrument and invest according to each investor's risk tolerance. This research has several limitations, such as the short research period, namely from January 2018 – December 2022. For future research, it would be advised to widen the period of data that is going to be researched, and a wider variety of investment instruments would also be a welcome improvement as they can provide research results that would be more beneficial and extensive.